Water mass composition in Fram Strait determined from the combination of 129I and 236U: Changes between 2016, 2018, and 2019 - A.-M. Wefing; N. Casacuberta; M. Christl; P. A. Dodd (Frontiers in Marine Science, 2022)
Changes in the provenance and composition of waters exported from the Arctic Ocean have the potential to impact large-scale ocean circulation processes in the sub-polar North Atlantic. The main conveyor of waters from the Arctic Ocean to lower latitudes is the East Greenland Current (EGC), flowing southward through Fram Strait. It is therefore crucial to determine and monitor the composition of the EGC, a mixture of polar waters of different origins. Here we present a pilot study on the potential of the long-lived anthropogenic radionuclides 129 I and 236 U as tracers of the EGC water mass composition, based on a time series of 236 U and 129 I concentrations measured across Fram Strait in the years 2016, 2018, and 2019. The overall spatial distribution of 236 U and 129 I was similar among the three sampling years, but a decrease in concentration was observed in the upper water column of the EGC. The observed changes could only partly be attributed to the transient nature of the radionuclide signals, but instead pointed to changes in the EGC water mass composition. To investigate these changes, 236 U and 129 I were first combined in a mixing model featuring the endmembers expected in the upper EGC. We distinguished between Pacific Water (PAC), Atlantic Water advected from the Arctic Ocean (ATL), and Atlantic Water recirculating in Fram Strait (RAC). In 236 U- 129 I tracer space, PAC and RAC showed similar tracer signatures, but were well distinguished from ATL. From 2016 to 2018/19, a decrease in the ATL fraction was evident for the upper EGC. Secondly, the respective combination of 236 U and 129 I with salinity showed differences in absolute water mass fractions, but similar temporal trends. Both suggested an increase in PAC of about 20% for the uppermost layer of the EGC (samples with potential densities below 26.5) and an increase in RAC of about 10−20 % for denser samples. 129 I and 236 U, in combination with salinity, were shown to be suitable tracers to investigate water mass composition in Fram Strait, with the advantage that they can distinguish Atlantic Water advected from the Arctic Ocean from that recirculating in Fram Strait.